ANALISIS POTENSI AIR PANAS DI BUKIT KASIH KANONANG UNTUK PENGERING GABAH - Reyvo Rully Dien; Tertius V Y Ulaan; Romels C A Lumintang (Fakultas Teknik Jurusan Teknik Mesin Universitas Sam Ratulangi, 2014)
This study is intended to analyze thehot spring water potential at Bukit KasihKanonang by studying the influence of water level toward the water contents reduction ofunhulled rice mass after drying process has been done.Unhulled rice drying process has been examined on the dryer for five days with thevaried water level. The examination was being done in five hourseach day, starts at 9.00a.m till 02.00 p.m WITA (the local time of middle Indonesia).The result of analysis shows that the percentage of the ideal water contentreduction stand on the position level water with height 15 cm which is 72.470 %. The mostoptimal heat transfer rate of the unhulled rice stands on level 10 cm with the drying timeof 5 hours and cross-sectional size of the dryer is 50 x 50 cm.Keywords : Hot spring Water, Unhulled-Rice Drying, Drying Temperature